Right to “Life”: The Cruel Contradiction of Exceptions to the Death Penalty for Pregnant People - Trejbalova, Tereza (The prison journal, 2024)
The death penalty debate intensifies when condemned women are considered, at least in part because of the associations society holds between womanhood and motherhood. Consequently, the concept of motherhood inherently permeates every condemned woman's sentence. Using qualitative document analysis, we examine how pregnancy is accounted for in the death penalty statutes and execution protocols. In half of U.S. states, exceptions exist in the statutes preventing executions of pregnant people, but pregnancy is rarely mentioned in execution protocols. The findings highlight aspects of reproductive injustice.